Registration status and outcome reporting of trials published in core headache medicine journals. (17th November 2015) - Rayhill, Melissa L.; Sharon, Roni; Burch, Rebecca; Loder, Elizabeth
Abstract : Objectives: To evaluate randomized controlled trial (RCT) registration and outcome reporting compliance in core headache medicine journals. Methods: We identified RCTs published in core journals ( Headache, Cephalalgia, and the Journal of Headache and Pain ) from 2005 through 2014. We searched articles for trial registration numbers, which were verified in the corresponding trial registry. We categorized trial funding sources as industry, academic, government, or mixed. We contacted corresponding authors to assess reasons for nonregistration. We evaluated whether primary outcomes in trial registries matched those in corresponding publications. Results: The journals published 225 RCTs over the study period. Fifty-eight of 225 (26%) reported a trial registration number in the article that could be linked to a corresponding registry entry. Trial registration rates increased over the 9 years of the study. Forty-six of 118 (39%) of industry-funded studies were registered compared with 27% of academic and 0% of government-funded studies. Only 5% of RCTs were prospectively registered, reported primary outcomes identical to those in the trial registry, and did not report unacknowledged post hoc outcomes. The most common reason for nonregistration was lack of awareness. Conclusions: Only about a quarter of the articles published in the core headache medicine journals are compliant with trial registration, but compliance has increased over time. Selective reporting of outcomes remains a problem, and very few trials met all 3 reporting standards assessed in this study. Efforts to improve the quality of trial reporting in the headache literature should continue.